2023
DOI: 10.3390/cancers15061812
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of HPV Extended versus Partial Genotyping for Cervical Cancer Screening in Singapore

Abstract: Human papillomavirus (HPV) partial genotyping (PGT) identifies HPV16 and HPV18 individually, alongside 12 other high-risk HPV genotypes (hrHPV) collectively. HPV extended genotyping (XGT) identifies four additional hrHPV individually (HPV31, 45, 51, and 52), and reports the remaining eight in three groups (HPV33|58; 56|59|66; 35|39|68). Quality-adjusted life years (QALY), health care resource use, and costs of XGT were compared to PGT for cervical cancer screening in Singapore using DICE simulation. Women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…We identified two studies (the United States and Singapore) that found extended genotyping (three HPV groups) was likely to be considered cost-effective over partial genotyping; however, they did not consider the potential of age-specific algorithms alongside extended genotyping. 7,8 Under the majority of our sensitivity analyses, including for a vaccine-naive cohort, we found that age-based triage remained preferred, except when we assumed imperfect screening adherence.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We identified two studies (the United States and Singapore) that found extended genotyping (three HPV groups) was likely to be considered cost-effective over partial genotyping; however, they did not consider the potential of age-specific algorithms alongside extended genotyping. 7,8 Under the majority of our sensitivity analyses, including for a vaccine-naive cohort, we found that age-based triage remained preferred, except when we assumed imperfect screening adherence.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, our study is one of the first to explicitly quantify the efficient gains through age‐ and genotype‐specific algorithms under uniform primary HPV testing for a vaccinated cohort. We identified two studies (the United States and Singapore) that found extended genotyping (three HPV groups) was likely to be considered cost‐effective over partial genotyping; however, they did not consider the potential of age‐specific algorithms alongside extended genotyping 7,8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…found that the cost of single-visit screening strategies at an HIV clinic in Kenya was lower than two-visit strategies, and HPV DNA testing was the most effective strategy when screening and treatment were provided in a single visit ( 66 ). Conversely, alternative strategies such as HPV genotyping and visual inspection with acetic acid may be optimal in other contexts ( 37 , 67 70 ). Lew et al.…”
Section: Discussionmentioning
confidence: 99%